KULIAH SAMBIL BEKERJA pada Kalangan Mahasiswa Perantau di Kota Denpasar - Sudarzahmo, Ramdan Putra; Laksmiwati, Ida Ayu Alit; Aliffiati, . (Sunari Penjor : Journal of Anthropology; Vol 8 No 2 (2024): Volume 8. No. 2. September 2024, 2024)
The phenomenon of overseas students who work is often found in the Denpasar City where studying while working can have an impact on overseas student. This research aims to understand the adaptation strategies of overseas students who study while working in the Denpasar City. The method used in this research is a qualitative method by collecting data through observation and in-depth interviews. The results of the study show that students who choose to study whilw working wre based on several factors, such as economic factors (needs), to gain experience, and the desire to be more independent. In addition to the factors that affect a student studying while working, several adaptatioan strategies for overseas students studying while working in the Denpasar City include: adapting to a new environment, dividing study time with working time, and forming a support system.